"I felt like I was left on my own": A mixed‐methods analysis of maternal experiences of cesarean birth and mental distress in the United States. Issue 3 (1st March 2021) - Sega, Annalisa; Cozart, Ashley; Cruz, Andrea Ocasio; Reyes‐Foster, Beatriz
Abstract: Background: Postpartum depression (PPD) is the most common complication of childbearing. Understanding potential contributors, such as cesarean deliveries, is essential to improving maternal mental health. This study investigated the relationship between unplanned versus planned cesarean birth and postpartum depressive symptoms. Methods: We employed a sequential, mixed‐methods approach wherein the Edinburgh Postnatal Depression Scale (EPDS) was first administered to participants who had experienced a cesarean birth within the previous 12 months. EPDS scores among those in the unplanned vs. planned cesarean groups were compared by means of SPSS. Twenty‐five participants with EPDS scores >8 were then interviewed to provide subjective measures of maternal well‐being. Interview data were subjected to thematic qualitative analysis using a modified grounded theory approach. Results: The average EPDS score from 120 participants with unplanned cesareans was 10.7 ± 6.4, with 68.5% scoring >8. The average EPDS score from 93 participants with planned cesarean births was 8.96 ± 5.7, with 52.7% scoring >8. The difference in mean score was statistically significant ( P  < 0.05). Interview findings revealed several important themes including: support, medical interaction, stress, recovery, breastfeeding, and sleep. In several cases, participants were not properly screened, or screening tool responses were ignored. Numerous participants reported medical interactions where they felt ignored by practitioners, including one interviewee who stated, "I got my tubes tied because it was so traumatizing that I never wanted to give birth again." Discussion: Findings suggest that unplanned cesareans have a higher incidence and severity of postpartum depressive symptoms. Interview analyses highlight important areas for improvement and concern about the current state of postpartum mental health care and physician‐guided supports in this US sample.